Pengaruh Budaya Hukum Terhadap Penegakan Hukum Tindak Pidana Korupsi Dalam Dunia Pendidikan Di Indonesia - Surbakti, Anton Diary S.; Lubis, Aldira Ardiansyah; Zebua, Johan Teguh (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to determine: (1) the rules for the enforcement of corruption in  Indonesia, (2) the influence of the culture of rules on the enforcement  of  the  rules  for  corruption in Indonesia, (3) the efforts of educational forums to eradicate corruption  in Indonesia The  procedure  for  collecting  and  collecting  data  used  in  this  research  is  through  a literature  study/documentary  study,  using  relevant  regulatory  materials,  collecting materials  that  will  be  used  in  this  research,  conducting  searches  to  find  relevant regulatory materials. using Legal Culture and Criminal Acts of Corruption in  efforts  to overcome  Corruption  Crimes  in  global  education  in  Indonesia.  Through  this   data collection technique,  it  is  necessary  to  find  a  concept  that  can  answer  the  news  of  the rules in this study. Based  on  the  output  of  this  study,  it  appears  that  the  eradication   of   corruption  by the government has not resulted in  the  required  output.  The  complexity  of  the  fight  against  corruption  in  Indonesia  is  apparently  not  relatively  solved  by  relying  on  preventive and investigative tactics, but also educative tactics.